Financial stability: To regulate or not? A public choice inquiry - Vo Phuong Mai Le; David Meenagh; Patrick Minford (Cardiff University, Cardiff Business School, 2018)
The paper takes the stand that the central banks as financial regulators have their own interest in imposing more regulations. It models the institutional behaviour for the central bank and government using the Indirect Inference testing and estimation method as it finds a set of coefficients of the model that can generate the actual observed behaviour for the US. The paper establishes that good monetary policy can reduce instability. Regulation at worse destabilises the economy and at best contributes little to stabilise the economy. After the financial crisis, financial regulations were too severe and thus actually increased instability.
Keywords: E10; E58; G28; 330; DSGE; Regulations; Financial Stability; Monetary Policy